Modeling the Environmental Fragility of the Perdizes River Sub-Basin, Triângulo Mineiro, Minas Gerais (Revista Espinhaço, 2026)
Assessing environmental fragility is essential to identify ecological vulnerabilities, guide sustainable practices and prevent the degradation of natural resources, ensuring the preservation of ecosystems and the well-being of future generations. The objective of this work was to map the environmental fragility of the Perdizes River Sub-basin, Monte Carmelo, Minas Gerais, Brazil. The characteristics of soil, relief, geomorphology, proximity to bodies of water, slope and land use and cover, through a multi-criteria analysis, were used to evaluate Potential Fragility (natural characteristics) and Emergent Fragility (natural and anthropogenic characteristics). The analysis of potential fragility found that 96.26% of the basin's total area is in the low and medium fragility categories, indicating that the region, naturally, presents a certain degree of ecodynamic landscape stability. As for emerging fragility, the medium and high categories predominate, which corresponds to 87.37% of the total area, indicating the effect of anthropogenic impact on an ecosystem. Areas with high or very high fragility are associated with cambisols, which have low fertility and are more prone to erosion. When combined with human activities, there is a worsening of emerging fragility, mainly resulting from pasture in the northern part of the area. The research concludes that human actions have a significant impact on the environmental fragility of the area, especially in naturally sensitive areas.
Keywords: Ecosystem Management; Watershed Management; Ecodynamic Units; Environmental Planning; Geographic Information Systems